An Empirical Study of Environmental Noise Pollution of Tuticorin District of Tamilnadu, India - Amutha, D. (International Journal of Bio-resource and Stress Management, 2023)
Noise is a disturbance to the human environment that is escalating at such a high rate that it will become a major threat to the quality of human lives. This study identifies the sources of noise that create noise pollution. Moreover, the study explores the effects of noise on the sample respondents and their reactions. Finally, various measures to control the pollution are contemplated. The empirical evidence gathered through this study can be employed for developing appropriate legal and public action programme. This empirical study is based on a sample survey of the Tuticorin District of Tamilnadu. 400 respondents were interviewed personally. The data relates to the month of August 2010. Percentage analysis, averages, standard deviation, standard error, F test, chi-square tests, Cramer’s V and probability analysis were used. The analysis indicates that a very large proportion of respondents in each age group are being affected by noise emanating from the loudspeakers. A very large proportion of respondents feel that noise interferes with inter-personal communication and causes annoyance. However, there is a much higher incidence of deafness effects on old people. Public education appears to be the best methods as suggested by the respondents.